Legal capacity and biomedicine: Biomedical discrimination - Cvetić Radenka (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
The article begins with the overview of the legal capacity as a general legal qualification recognized by the legal order guaranteeing the right to be a holder of rights and obligations. The article is then focused on the scope of the absolute Constitutional guarantee of the right to legal personality as well as on the Constitutional prohibition of discrimination which gives rise to the general equality before the Constitution and the law. The focus of this article is the moment when the legal capacity, or legal personality, is considered to be acquired. It then moves to the issue whether limiting the access to techniques of assisted reproduction (biomedical conception) is contrary to the general rules on legal capacity, and whether this is a genuine form of biomedical discrimination.